A Source Problem for the Helmholtz Equation via a Dirichlet-to-Neumann Map. (23rd August 2021) - Lee, Kuo-Ming
Abstract : In this paper, we consider a source problem for a time harmonic acoustic wave in two-dimensional space. Based on the boundary integral equation method, a Dirichlet-to-Neumann map in terms of boundary integral operators on the boundary of the source is constructed to transform this problem into two boundary value problems for the Helmholtz equation.